Law No. 79 of the year 1975 Promulgating the Social Insurance law = قانون التأمينات الاجتماعية. (2025)
1. Social insurance scheme, scope application and definition -- 2. Establishment, finance and management funds -- 3. Old age, disability and death insurance -- 4. work injuries insurance -- 5. Illness insurance -- 6. On establishing a fund for the treatment of disease and work injuries, its finance, management and competences -- 7. Unemployment insurance -- 8. Social care insurance for pensioners -- 9. Beneficiaries and coditions of their entitlement -- 10 Additional entitlements -- 11 General provisions -- 12. Provisional and transitional provisions -- 13. Penalties